2019
DOI: 10.1111/dar.12995
|View full text |Cite
|
Sign up to set email alerts
|

Understandings of the component causes of harm from cigarette smoking in Australia

Abstract: Introduction and Aims To investigate relationships between smoking‐related behaviours and knowledge of the disease risks of smoking and the causes of smoking harms, using a four‐way division of ‘component causes’: nicotine, other substances found in unburned tobacco, combustion products of tobacco and additives. Design and Methods The data were collected using an on‐line survey in Australia with 1047 participants in three groups; young non‐smokers (18 to 25), young smokers (18 to 25) and older smokers (26 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…We have avoided being over-confident in prescribing solutions, as there is still more to understand about the problem. Nonetheless, our published quantitative survey research demonstrated that some of the misunderstandings discussed here are likely to be prevalent, particular those concerning harm from additives (King et al, 2019). Recent research in the United States (Bernat et al, 2017; Brewer et al, 2017) has also found these beliefs to be widespread, so it is unlikely that our findings are due to a chance selection of participants with unusual beliefs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We have avoided being over-confident in prescribing solutions, as there is still more to understand about the problem. Nonetheless, our published quantitative survey research demonstrated that some of the misunderstandings discussed here are likely to be prevalent, particular those concerning harm from additives (King et al, 2019). Recent research in the United States (Bernat et al, 2017; Brewer et al, 2017) has also found these beliefs to be widespread, so it is unlikely that our findings are due to a chance selection of participants with unusual beliefs.…”
Section: Discussionmentioning
confidence: 93%
“…Recent research on public understandings of smoking-related chemicals, using both qualitative and quantitative methods (Bernat et al, 2017; Breslin et al, 2018; Brewer et al, 2017; King et al, 2018, 2019; Moracco et al, 2016; Morgan et al, 2017; Pepper et al, 2017), has yielded a consistent picture: the public has limited knowledge of the toxicants in cigarette smoke and frequently believe toxic additives are the main cause of harmful exposures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, tobacco risk communication often presents information about nicotine in tobacco products together with information about the risk of tobacco products, which can make people develop negative feelings or affect towards nicotine. Such negative affect is related to high perceived nicotine risk [27,28] and can bias processing of nicotine-related messages. In our study, this negative affect might even get reinforced due to the presence of negative information about nicotine in the fact sheet.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, communication with the public concerning risks of tobacco use generally conflates information about nicotine in tobacco products with information about the dangers of tobacco products. This exacerbates the misperception that nicotine is a known carcinogen 22 . This notion was upheld by a survey of the public about low‐nicotine cigarettes.…”
Section: Introductionmentioning
confidence: 99%